Kashmir : A Disputed Legacy, 1846-1990 - Lamb, Alastair (Karachi Oxford University Press, 1992)
The Kashmir dispute has dominated Indo-Pakistan relations ever since independence, fifty years ago. It has also played a major part in the genesis of the Sino-Indian boundary dispute. In this award-winning book, Alastair Lamb examines the history of this dispute.
Include Maps, Bibliography and Index.
Keywords: India--Jammu and Kashmir -- Pakistan -- India -- Diplomatic relations -- Politics and government